Molecular characterization and expression analysis of two crucial MAPKs‐ jnk1 and erk1 as cellular signal transducers in Labeo rohita in response to PAMPs stimulation and pathogenic invasion. Issue 3 (22nd January 2020) - Sadangi, Sushmita; Mohanty, Arpita; Paichha, Mahismita; Samanta, Mrinal
Abstract: Mitogen‐activated protein kinases (MAPKs) are crucial Ser/Thr protein kinases that play important roles in innate immunity by converting extracellular stimuli into a wide range of cellular responses, including the production of cytokines. In this study, two MAPK genes, jnk1 and erk1, were cloned and characterized in rohu ( Labeo rohita ), a commercially important freshwater fish species in the Indian subcontinent. In healthy rohu, both jnk1 and erk1 gene expressions were highest in the spleen as compared to gill, liver, blood and kidney tissues. In vitro stimulation of the L. rohita gill (LRG) cell line with γ‐D‐glutamyl‐meso‐diaminopimelic acid, muramyl dipeptide and polyinosinic: polycytidylic acid (poly I:C) resulted in significantly enhanced expressions of jnk1 and erk1 genes. In the in vivo experiments, jnk1 and erk1 gene expressions were also enhanced in lipopolysaccharides and poly I:C‐treatment. Infection of rohu fingerlings with Aeromonas hydrophila and Bacillus subtilis revealed significantly enhanced expressions of the jnk1 and erk1 genes in all of the tested organs/tissues. Together these results imply the important role of jnk1 and erk1 genes in fish during pathogenic invasion and diseases.